Kemampuan berpikir kreatif matematis siswa dalam menyelesaikan soal lingkaran ditinjau dari habits of mind - Wathoni, Muhammad Hizbul; Negara, Habibi Ratu Perwira (Journal of Didactic Mathematics, 2024)
Mathematical creative thinking ability is a student's ability to create or find new ideas in solving a problem. Everyone must have the ability to think creatively, especially students. The ability to think creatively plays an important role in the progress of every student. However, in reality, many students are not able to solve a problem using their creative thinking skills. This is possible because students do not get used to thinking (habits of mind). This research aims to determine students' mathematical creative thinking abilities in solving circle problems in terms of habits of mind. The method used in this research is a qualitative method with a case study type of research. There are three data collection techniques used, namely: tests, questionnaires and interviews. The results showed that 6 subjects who had high habits of mind were able to show all indicators of mathematical creative thinking ability, 12 subjects who had moderate habits of mind were able to show three indicators of mathematical creative thinking ability and 3 subjects who had low habits of mind were only able to show one indicator of mathematical creative thinking ability. So, habits of mind have an impact on students' mathematical creative thinking abilities.